Aplikasi Ijtihad Intiqa’iy Dan Insya’iy Dalam Kehidupan Modern (Studi Tentang Fatwa Komisi Fatwa Majelis Ulama Indonesia Dalam Penerapan Konsep Ijtihad Intiqa’iy Dan Insya’iy Tahun 2004 Tentang Bunga Bank Dan Terorisme) - Ahmad Insya’ Ansori (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2014)
Special Method cases Ijtihad against contemporary need to look for legal status has been professed as a solution by the Prophet Muhammad tens of centuries ago . In time, a systematic and logical method initiated by Yusuf Abdullah al - Qaradawi is Intiqa'iy and Ijtihad Ijtihad Insya'iy now adopted by the Indonesian Ulama Council Fatwa Committee as a method of problem solving Interest and Terrorism in 2004.